High uptake of COVID-19 vaccines among healthcare workers in urban Uganda - Kyakuwa, Nasimu; Kimbugwe, Geofrey; Nakanjako, Flavia; Kalute, Hamza; Mpooya, Simon; Atuhairwe, Christine; Perez, Laurent; Kikaire, Bernard (Public Library of Science, 2024)
The aim of the study was to describe the facilitators, barriers to and level of uptake of COVID-19 vaccines among healthcare workers in primary healthcare facilities in an urban setting in Uganda. We conducted a cross-sectional study among HCWs in private and public health facilities in Entebbe municipality between July 2021 and August 2021. Data was collected using a structured questionnaire that was shared, via an online link, to consented participants. Uptake of the vaccines among healthcare workers was analysed as proportions, and logistic regression was used to analyse barriers and facilitators to uptake of COVID-19 vaccines. The study enrolled 360 participants, with 61.7% (n = 222) females. A total of 236 (65.6%) healthcare workers had received at least one dose of COVID-19 vaccine, with higher uptake among females 64% (n = 151). Age above 40 years (OR 2.16), working in a government healthcare facility (OR 3.12), participating in COVID-19 vaccine related activities (OR 4.62), and having tested for SARS-COV-2 (OR 3.05) increased the odds of having been vaccinated. Working in small roadside clinics reduced the odds of being vaccinated by almost 70%, while HCWs in government health services were 3.1 times more likely to have been vaccinated. History of having cared for a COVID-19 patient and having a positive SARS-COV-2 test result did not influence the uptake of the vaccines in the study population. Vaccine uptake among HCWs was close to the World Health Organisation (WHO) recommended uptake of 70% by mid-2022.
Keywords: COVID-19 vaccines; healthcare workers; urban Uganda